Computers Helping People with Special Needs 12th International Conference, ICCHP 2010, Vienna, Austria, July 14-16, 2010. Proceedings - Miesenberger, Klaus; Klaus, Joachim; Zagler, Wolfgang; Karshmer, Arthur; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
Welcome to the Proceedings of ICCHP 2010! We were proud to welcome participants from more than 40 countries from all over the world to this year$1 (Bs ICCHP. Since the late 1980s, it has been ICCHP$1 (Bs mission to support and reflect development in the field of (3z(BAssistive Technologies,(3y (BeAccessibility and eInclusion. With a focus on scientific quality, ICCHP has become an important reference in our field. The 2010 conference and this collection of papers once again fulfilled this mission. The International Programme Committee, comprising 106 experts from all over the world, selected 147 full and 44 short papers out of 328 abstracts submitted to ICCHP. This acceptance ratio of about half of the submissions demonstrates our strict pursuit of scientific quality both of the programme and in particular of the proceedings in your hands. An impressive number of experts agreed to organize (3z(BSpecial Thematic Sessions(3y (B(STS) for ICCHP 2010. These STS help to bring the meeting into sharper focus in several key areas. In turn, this deeper level of focus helps to collate a state of the art and mainstream technical, social, cultural and political developments.s
Design for Adaptive Content Processing -- Digital Access to Documents for People with Print Disabilities -- HCI and Non Classical Interfaces -- HCI: Software Accessibility and Social Interaction -- Entertainment Software Accessibility -- Accessible Tourism -- Smart and Assistive Environments -- Usable Web Accessibility: Editing -- Usable Web Accessibility: Education and Motivation -- Usable Web Accessibility: Evaluation -- eGovernment Accessibility -- Accessibility of Blended and E-Learning for Mature Age and Disabled Students and Staff -- Successful Service Provision -- Standards: A Driver for Accessibility and Usability -- People with Speech Impairment: (3z(BWeak and Silent Speech(3y(B: Tools to Support People with Speech Impairment -- People with Speech Learning and Cognitive Problems: Easy-to-Web.s
Keywords: Computer science; Multimedia information systems; User interfaces (Computer systems).; Computer graphics; Education -- Data processing; Computers and civilization; Computer Science; User Interfaces and Human Computer Interaction; Information Systems Applications (incl. Internet).; Computers and Society; Multimedia Information Systems; Computer Imaging, Vision, Pattern Recognition and Graphics; Computers and Education; Electronic books